Pearl millet grain for beef cattle in crop-livestock integration system: intake and digestibility - Alonso, Marcell Patachi; Bevitori Kling de Moraes, Eduardo Henrique; Pereira, Dalton Henrique; Pina, Douglas dos Santos; Mombach, Mirceia Angele; Hoffmann, Alvair [UNESP]; Gimenez, Breno de Moura; Medeiros Sanson, Renan Marcelo (Univ Estadual Londrina, 2017)
The present study aimed to evaluate the nutritional parameters (intake and digestibility) of beef cattle in two genetic groups fed protein-energy supplements formulated by different levels of replacement of maize with pearl millet grain during the dry season. Sixty-four uncastrated young bulls, with an average age of 20 months and an initial body weight of 388 +/- 26 kg, were included in the study. The experimental area consisted of four paddocks approximately 4.7 ha in size, composed of Brachiaria brizantha `Marandu' within a crop-livestock integration system. The study was based on a completely randomized factorial design (2x4). Two genetic groups (Crossbred and Nellore) and the effects of replacement of maize with pearl millet grain at 0%, 33%, 66%, and 100% in the supplement formulations were assessed. No significant effects were observed in the genetic groups and with the replacement of maize with pearl millet grain, as well as in the pasture total dry matter (DM) and nutrients intake, or the coefficients of total digestibility of nutrients. The dietary concentration of digested organic matter was not influenced by the replacement levels of pearl millet grain, with values of 514.88, 515.76, 516.01, and 515.98 g kg(-1) of DM recorded for the 0%, 33%, 66%, and 100% replacement levels, respectively. Therefore, pearl millet grain can be utilized as a partial or total substitute for maize grain as the energetic ingredient in concentrated supplements for Nellore and crossbred beef cattle in pastures managed in crop-livestock integration systems.
Keywords: Replacement levels; Pasture; Drough; Supplementation